2021
DOI: 10.5812/ijp.108534
|View full text |Cite
|
Sign up to set email alerts
|

Which of the Anthropometric Parameters and Hormonal Variables in Prepubertal Children Are Correlated to True Micropenis?

Abstract: Background: Most issues of micropenis boys include poor body image and quality of life. Objectives: The purpose of this assay was to survey the relationship of anthropometric measures, testosterone, estradiol, gonadotropins and prolactin with stretched penile length (SPL) and flaccid glans-pubis length (GPL) in pre-pubertal boys with true small penis. Methods: This was prospective a cross-sectional observational study that was conducted in Imam Reza Hospital, Tehran, Iran from February 2015 to May 2020. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
(21 reference statements)
0
14
0
Order By: Relevance
“…They evaluated psychological disorders using the General Health Questionnaire (GHQ-28) and documented that constipated cases had significantly higher levels of anxiety (P < 0.022) compared to children without FC as the control group (16). In another study, Rezakhaniha et al found out that the flaccid measurement could be as helpful as stretched measurement if it is done from pubic bone to tip of glans (17). Furthermore, Rezakhaniha et al mentioned that penile length was positively correlated with height and testosterone but not with weight and estradiol in non-obese and obese children (18).…”
Section: Discussionmentioning
confidence: 99%
“…They evaluated psychological disorders using the General Health Questionnaire (GHQ-28) and documented that constipated cases had significantly higher levels of anxiety (P < 0.022) compared to children without FC as the control group (16). In another study, Rezakhaniha et al found out that the flaccid measurement could be as helpful as stretched measurement if it is done from pubic bone to tip of glans (17). Furthermore, Rezakhaniha et al mentioned that penile length was positively correlated with height and testosterone but not with weight and estradiol in non-obese and obese children (18).…”
Section: Discussionmentioning
confidence: 99%
“…Pubertal delay, infertility, and cryptorchidism were observed in LS (10). The treatment of sexual dysfunction and improvement of long-term gonadal function in LS have become increasingly important because some advances in kidney replacement therapy led to significantly improved life expectancy and more active life (10,20,21). New clinical trials for the treatment of polycystic kidney disease and Bard-Biddle syndrome have prescribed rapamycin.…”
Section: Diagnosismentioning
confidence: 99%
“…Body mass index (BMI) = Weight (kg)/Height 2 (m 2 ). BMI ≥30 was considered obese and 25-30 overweight, 19-25 normal and ˂19 underweight (Rezakhaniha et al, 2021). Beurer scale (Germany) was used for measuring of weight (kg) without shoes and with light clothing with limitation accuracy of 100 g. Height measurement (cm) was performed with a standing meter without shoes with limitation accuracy 0.5 cm.…”
Section: Participantsmentioning
confidence: 99%